Centra aktywności seniorów jako odpowiedź na wykluczenie społeczne osób starszych w obszarze bezpieczeństwa społecznego - Grzegorz Sudoł (Edukacja Ustawiczna Dorosłych)
The article presents the issue of social security in the context of seignior policy in the area of a commune and multi-sector partnership. It takes up the challenge of diagnosing the needs, defining and presenting the goals, functions and tasks of the Seigniorial Services Centers. Moreover, the possibilities of cooperation and the use of personal, material and financial resources in the implementation of programs and projects supporting the elderly in their holistic development are presented in the paper. The influence of the local environment on the functioning of some Centers has also been analysed.